MONITORING OF LANDSLIDE PROCESSES ON URBAN TERRITORIES AFTER THE EXAMPLE OF KYIV - HOLUB, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article exposes peculiarities of creation of monitoring system on territories of cities, which are considered as a specific system. Modern complex of studying of dynamical conditions of landslide slopes in Kyiv is presented. The article gives principles of monitoring of landslide processes in Kyiv.